2021
DOI: 10.3390/healthcare9121691
|View full text |Cite
|
Sign up to set email alerts
|

Structural Factors and Quality of Diabetes Health Services in Hail, Saudi Arabia: A Cross-Sectional Study

Abstract: The chronic disease burden in Saudi Arabia has created adverse health, social and economic consequences that require urgent attention from health and political authorities. Diabetes has become an epidemic in Saudi Arabia. Data on personal and structural factors associated with diabetes in the Hail region are scarce. Such data are imperative to develop effective strategies to control the epidemic in the region. A cross-sectional study of diabetes patients attending diabetes health care facilities in Hail was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…One of the primary objectives of the Vision, 2030 guidelines is to achieve economic as well as health prosperity in KSA by the year 2030, that which has recognized the complete eradication of health discrepancies in chronic disease patients as an utmost priority of public health ( Chowdhury et al, 2021 ) ‘ Vision, 2030 - Quality of Life (QOL) program’, has targeted diabetes which is a critical chronic disease condition. The foremost strategies of this initiative in controlling and preventing diabetes include improvement of the acceptability and ease of access to treatment as well as preventative healthcare services for patients with diabetes across different regions of KSA ( Itumalla et al,2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary objectives of the Vision, 2030 guidelines is to achieve economic as well as health prosperity in KSA by the year 2030, that which has recognized the complete eradication of health discrepancies in chronic disease patients as an utmost priority of public health ( Chowdhury et al, 2021 ) ‘ Vision, 2030 - Quality of Life (QOL) program’, has targeted diabetes which is a critical chronic disease condition. The foremost strategies of this initiative in controlling and preventing diabetes include improvement of the acceptability and ease of access to treatment as well as preventative healthcare services for patients with diabetes across different regions of KSA ( Itumalla et al,2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Saudi Arabia comparing people with ACEs to those without ACEs revealed a two-fold greater risk of physical health problems such as hypertension, T2DM, coronary heart disease, and obesity among people with ACEs [ 13 , 30 , 31 ], agreeing with another study conducted in Saudi Arabia [ 19 ]. This high prevalence of ACEs in Saudi Arabia might contribute to high rates of T2DM in Saudi Arabia, as supported by the WHO ranking, which puts Saudi Arabia in second place among Middle Eastern countries with a high rate of diabetes and seventh highest worldwide [ 32 , 33 ]. Further, a recent study evaluating the prevalence of T2DM in Saudi Arabia from 1999 to 2022 estimated it to be 29.2% in 2011 and 44.1% in 2022 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that the presence of good-quality health care professionals working in diabetes centers can contribute to patients' satisfaction with the services they received. 8 Moreover, to expand services in underserved areas, the Ministry of Health should partner with other sectors including transportation, water, and power, as well as social security services. 9 To make sure a successful process and achieve good diabetic outcomes, it is imperative that appropriate infrastructure items are in place.…”
Section: Discussionmentioning
confidence: 99%